Exploring the Influence of Learning Difficulties and Self-Directed Learning on Problem-Solving Ability in Elementary School Students: The Mediating Impact of Mathematical Disposition - Rahmawati, Silvi Fitria; Daryono, Rihab Wit; Kurniawati, Annisa Dwi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Mathematical disposition can help students overcome difficulties in learning mathematics more effectively. With the mediation of mathematical disposition, the positive influence of self-directed learning can more easily lead to increased students' problem-solving abilities. This research aims to explore the role of mathematical disposition as a mediator in influencing learning difficulties and self-directed learning on problem-solving abilities. The survey method was used to collect data based on probability sampling from 32 students from class 5 at MI Ma'arif Patihan Wetan. Data collection was carried out using a questionnaire consisting of a Likert scale with 4 alternative answers. PLS-SEM analysis was used to analyze data and test and evaluate the construction of variables measuring problem-solving abilities. The results of the analysis show that problem-solving abilities are not significantly influenced by learning difficulties (β=0.000; ρ=0.998) and self-directed learning (β=0.000; ρ=0.061). In addition, mathematical disposition was proven to mediate the influence of learning difficulties (β=0.443; ρ=0.000) and self-directed learning (β=0.214; ρ=0.286) on problem-solving abilities. These findings highlight the importance of mathematical disposition in facilitating problem-solving abilities through learning difficulties and self-directed learning. The practical implication of this research is the need for a holistic approach in developing a positive attitude towards mathematics as an integral part of the learning approach. This research supports efforts to provide a learning environment that supports, motivates, and encourages students to develop positive mathematical dispositions. As well as emphasizing the development of metacognitive skills and utilizing learning technology to facilitate interaction and collaboration between students in exploring mathematical concepts.